Lower Boundary Conditions and Pricing Efficiency Testing of Indian Index Options Market : Empirical Evidence from Nifty 50 Index - Mutum, Kelvin; Das, Ashim Kr. (Indian Journal of Finance, 2019)
This article examined the pricing efficiency of the Nifty 50 index options market by empirically testing the lower boundary conditions (LBCs), a model - free approach. The study covered a period from April 1, 2012 to March 31, 2018. The violations of LBCs indicated that options were underpriced (mispriced). The frequency and magnitude of mispriced signals were examined according to liquidity and maturity of the options contracts. This was done with the view that mere mispricing of options does not indicate inefficiency of the market. It is the opportunity to extract abnormal profit (arbitrage) from these mispriced signals which poses a serious threat to the market efficiency. It was observed that most of the mispriced signals were concentrated at the thinly traded region and options which were going to get expired. The magnitude of mispriced signals at the thinly traded region and options which were going to get expired was significantly larger than the moderately and highly traded levels and options, which were far away from the maturity date. Furthermore, in order to validate whether the differences in the magnitude of violations were statistically significant, the hypotheses were formulated and tested for both the call and put options. The results of the study suggested that the Indian index options market during the period of study was efficient as most of the mispriced signals were not exploitable due to lack of liquidity.